Strategic management accounting information usage and the choice of competitive strategy: moderating role of corporate life cycle / Pu Zhao, Raman Noordin and Stephen Laison Sondoh Jr - Pu, Zhao; Zhao, Pu; Noordin, Raman; Sondoh Jr, Stephen Laison (UiTM Press, 2023)
This research investigated the moderating role of the corporate life cycle between Strategic Management Accounting (SMA) information usage and the choice of competitive strategies. The current research demonstrates that SMA information usage has a positive effect on the choice of competitive strategies by using partial least squares structural equation modelling (PLS-SEM) and comparing the difference in the relationship between SMA information usage and the choice of competitive strategy in different life cycle stages through partial least squares multigroup analysis (PLS-MGA). We found that compared with companies in the maturity stage, the productrelated information usage by companies in the growth stage was helpful for the choice of differentiation strategy. In addition, compared with companies in the growth stage, companies in the maturity stage used product-related information and competitor-related information to help managers choose cost leadership strategies. This research clarifies the relationship among the corporate life cycle, SMA information usage and the choice of competitive strategy, provides managers with more accurate strategic decision-making suggestions, and provides a method for corporate life cycle research, that is, using PLS-MGA to compare path differences in variable relationships at different life cycle stages.